Employing personal health records for population health management - Kostadinovska, Ana; de Vries, Gert-Jan; Geleijnse, Gijs; Zdravkova, Katerina (Springer, Cham, 2014)
Linking various sources of medical data provides a wealth of data to researchers. Trends in society, however, have raised privacy concerns, leading to an increasing awareness of the value of data and data ownership. Personal Health Records address this concern by explicitly giving ownership of data to the patient and enabling the patient to choose whom to provide access to their data. We explored whether this paradigm still allows for population health management, including data analysis of large samples of patients, and built a working prototype to demonstrate this functionality. The creation and application of a readmission risk model for cardiac patients was used as carrier application to illustrate the functionality of our prototype platform.
Keywords: Personal Health Records, Population Health Management